Asymmetric construction of quaternary α-nitro amides by palladium-catalyzed C(sp3)–H arylation. Issue 15 (27th January 2020) - Kong, Wei-Xin; Xie, Shi-Jing; Cao, Chen-Yao-Zi; Zhang, Chao-Wei; Wang, Chuanyong; Duan, Wei-Liang
Abstract : A Pd-catalyzed enantioselective C(sp 3 )–H arylation of N -( o -Br-aryl) anilides has been disclosed for the preparation of optically active quaternary amino acid derivatives. Quaternary α-nitro amides are constructed with stereoselectivities of up to 98% ee. Abstract : Pd-Catalyzed enantioselective C(sp 3 )–H arylation of N -( o -Br-aryl) anilides has been disclosed, and quaternary α-nitro amides were constructed with up to 98% ee. The presence of the nitro group on the substrate enables the progress of the reaction and the ready transformation of the product to optically active quaternary amino acid derivatives.